The THE POTRAYAL OF KING ARTHUR IN VIDEO GAMES FROM TRANSSTYLIZATION PERSPECTIVES: AN INTERTEXTUAL STUDY - Evita Peron (CrossOver, 2022)
Transstylization is a stylistic rewriting, a transposition whose main function is a change of style. It is concerned with the preparation of a text. In a stylistic rewriting of a text, it can be applied by stylization or superimposing additional stylistic elements onto a hypotext. This research attempts to reveal what transstylization techniques are applied on the portrayal of King Arthur in video game, which is adapted from the book entitled King Arthur Myth-Making and History, and how the transstylization generates losses and gains in the characterization of King Arthur. This study uses qualitative method that allows researcher to collect, analyze, and draw conclusions from  the data. The data of this research are in the form of visualization, characteristics, names, and stories that  are in accordance with the book entitled King Arthur Myth-Making and History. The data in this study were analyzed using Spradley’s technique of analysis. Transstylization by Gerard Genette and adaptation theory by Linda Hutcheon were applied to answer the problem in this research. 76 data were found in this research. From the data found, it was concluded that destylization is the dominant technique of transstylization in this research. This shows that the visualization, name and story of King Arthur in this research have a different pattern with the book. This research also shows how the transstylization causes losses and gains in the characterization of King Arthur in video games through the process Telling-Interacting. These findings contribute to knowledge about the transstylization of  King Arthur from the book entitled King Arthur Myth-Making and History into video games.